2010
DOI: 10.5114/aoms.2010.19291
|View full text |Cite
|
Sign up to set email alerts
|

Degree of genetic homozygosity and distribution of AB0 blood types among patients with spina bifida occulta and spina bifida aperta

Abstract: IntroductionAssuming that spina bifida (SB) is a genetically controlled disease, the aim of our study was to evaluate the degree of genetic homozygosity and the distribution of AB0 blood types among patients with SB occulta and SB aperta by the homozygously recessive characteristics (HRC) test.Material and methodsOur study included an analysis of the presence, distribution and individual combination of 15 selected genetically controlled morpho-physiological traits in a sample of 100 patients with SB (SB occult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Neural tube closure is a process involving interactions between genes, where environmental factors play significant role, pointing out the multifactorial inheritance of the spina bifida entity [24]. Beside the environmental factors that were studied broadly in several studies [8,24], as well as some molecular genetic observations, including the correlation of certain mutations on X chromosome and its influence on the SB formation [3,10,[25][26][27][28], a population-genetic approach, as a new method, can give a new insight on etiology for individuals with spina bifida [4,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural tube closure is a process involving interactions between genes, where environmental factors play significant role, pointing out the multifactorial inheritance of the spina bifida entity [24]. Beside the environmental factors that were studied broadly in several studies [8,24], as well as some molecular genetic observations, including the correlation of certain mutations on X chromosome and its influence on the SB formation [3,10,[25][26][27][28], a population-genetic approach, as a new method, can give a new insight on etiology for individuals with spina bifida [4,29].…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible explanations for the established differences in recessive homozygosity degree among different groups of affected individuals and the control [12,13,15,29,31]:…”
Section: Discussionmentioning
confidence: 99%
“…Hemivertebra is commonly associated with other skeletal anomalies [10], diastematomyelia [36], cardiac, urogenital, and gastrointestinal tract anomalies [8], and some syndromes, including Jarcho-Levin syndrome, Klippel-Fiel syndrome, VATER syndrome (vertebral anomalies, imperforate anus, tracheo-esophageal fistula, renal anomalies), VACTERL syndrome (VATER, cardiac and limb anomalies), OEIS (omphalocele, urinary bladder exstrophy, imperforate anus, and spinal anomalies), the Potter sequence, and spina bifida [11,35]. The most relevant form of spina bifida is myelomeningocele with the unfused neural processes of the lumbosacral spine, allowing the spinal cord to protrude through an opening [37,38]. Furthermore, detailed knowledge of the growth of vertebral ossification centers in the fetal period may be helpful in the prenatal detection of skeletal dysplasias (osteochondrodysplasias) resulting in a delay in appearance of ossification centers and poor mineralization, which is typical of osteogenesis imperfecta type II [12,39], achondrogenesis [40], thanatophoric dysplasia type I [12], and hypophosphatasia [41].…”
Section: Discussionmentioning
confidence: 99%
“…A difference in genetic variability between healthy individuals and those with a diagnosed SB was reported by Nikolic et al [19], but the possible role of gender for the SB individuals has not yet been observed regarding the individual traits variability.…”
Section: Discussionmentioning
confidence: 96%